Caregiver Burden In Caregivers Of Hospitalized Older Adults And Its Associated Factors - Jocabed Rocha-Balcázar; Carmen García-Peña; Lourdes Figueroa-Solano; Nicolas Castellanos-Perilla; Daniel Santiago Cortes-Sarmiento; Mario Pérez-Zepeda (Geriatrics, Gerontology and Aging)
AIM: Acute care has some complications in the older adult, a frequently overlooked complication is caregiver burden. Scarce information is available on this matter. Therefore, the objective is to describe the factors associated with caregiver burden at the moment of discharge of a hospitalized older adult, in the Mexican healthcare context. METHOD: This is a secondary analysis of a hospital. Bivariate and multivariate analyses were performed with caregiving burden (measured with the Zarit scale) as the dependent variable. Other variables were tested in order to assess their association with caregiver burden: sociodemographic, health-related, depression, functionality, social support and hospital length of stay, caregiver expenses, quality of life and satisfaction with received care. RESULTS: A total of 111 older adults with their respective caregivers were assessed. From this sample, the mean age for older adults was 73 years (± standard deviation 7.9 years) and 65.7% (n = 73) were women. Caregiver burden was present in 39.6% (n = 44) of the individuals. Regarding the multivariate analyses, the only variable independently associated with caregiver burden was depression in the older adult, odds ratio 1.12 (95% confidence interval 1–1.25, p = 0.045). CONCLUSIONS: In concordance with previous work on this matter, according to our results depression in the older adult was a trigger of caregiver burden at discharge of acute care.